The Use of Counseling Cognitive Behavior Therapy (CBT) Approach to Change Students' Attitudes toward Cheating Behavior at SMK 1 Gunung Talang - Emdorizal Emdorizal; Yeni Karneli; Marlina Marlina (International Journal of Applied Counseling and Social Sciences, 2019)
Students sometimes make cheating behaviors to achieve good grades in the exam. Cheating behavior is clearly cheating behavior that students should not do. The purpose of this study is to change the cheating behavior of students using the CBT approach, setting group. This study is a Quasi Experiment that uses quantitative methods and The Non-Equivalent Control Group Desig. The research subjects of class X of SMK Negeri 1 Gunung Talang was identified as having a tendency to cheat. The research instrument used a cheating behavior scale that fulfilled the requirements of the research instrument, then analyzed using the Wilcoxon Signed-Rank Test and the Kolmogorov Smirnov 2 Independent Samples test. The findings of this study show that in general CBT counseling group settings are effective for changing student attitudes toward cheating behavior. This finding can be discussed further.